In vitro shoot induction from petiole explants of tembesu (Fagraea fragrans Roxb) using 6-benzylaminopurine - Mayta Novaliza Isda; Riche Afrilla (Universitas Lancang Kuning, 2023)
Tembesu (Fagraea fragrans Roxb) is a valuable woody plant from the Loganiaceae family, utilized in construction and furniture production. Unfortunately, the tembesu population continues to decline due to excessive logging, forest fires, and a lack of cultivation efforts. Planting through seeds takes a long time, making in vitro propagation an attractive alternative. This research aims to evaluate the effect of 6-benzylaminopurine (BAP) in inducing shoots and determine the optimal BAP concentration on tembesu petiole explants in vitro. A completely randomized design (CRD) with six treatment levels (0, 0.5, 1, 1.5, 2, and 2.5 mg/L BAP) and five replications was employed. Despite a 10% shoot formation rate for each treatment, the optimal BAP concentration for callus formation was found to be 0.5 mg/L, with the highest percentage reaching 70%. The results indicate that adding different concentrations of BAP to the Murashige & Skoog (MS) medium was ineffective in inducing shoots in tembesu petiole explants. Therefore, further research and the development of more sophisticated in vitro propagation techniques are necessary to enhance the success of shoot induction in tembesu. It is hoped that this research will serve as a foundation and motivation for subsequent in-depth studies on the in vitro propagation of tembesu, supporting the conservation and development of this plant.